The dynamics of conflict management in organisations - Maulana, Afin; Andini, Eka Fitria; Herawati, Nadya Ayu (Psikologia: Jurnal Pemikiran dan Penelitian Psikologi, 2026)
Conflict is an inherent phenomenon in organizations arising from differences in interests, values, and individual perceptions. Although numerous studies have examined conflict management, existing research tends to be fragmented and has not comprehensively integrated the simultaneous roles of interpersonal communication and leadership style in influencing organizational performance and remains limited to specific sectoral contexts. This study aims to synthesize empirical and conceptual findings related to the dynamics of conflict management in organizations and to identify key factors influencing its effectiveness. The method employed is a literature review of 10 scientific articles published between 2021 and 2026, analyzed using a thematic approach. The findings indicate that organizational conflict is influenced by differences in interests, limited resources, communication barriers, as well as structural and cultural factors. Effective conflict management contributes to improved performance, productivity, job satisfaction, and the interpersonal relationship quality, whereas ineffective management leads to negative impacts on performance and team collaboration. In addition, open interpersonal communication and adaptive leadership are identified as key factors in successful conflict management. This study contributes by integrating perspectives on conflict management, interpersonal communication, and leadership into a more comprehensive analytical framework, while also highlighting the importance of contextual approaches in enhancing the effectiveness of conflict management in organizations.